A PREDICTION MODEL OF COMPANY HEALTH USING BAGGING CLASSIFIER - Green Arther Sandag (LPPM Nusa Mandiri, 2020)
In business, have many competitions between companies occur to obtain as many profits as possible, Financial Distress is a financial decline that occurs in companies, reflecting the health of the company before bankruptcy started. Therefore, to avoid bankruptcy, it requires a method or tool with high accuracy in identifying company health. This research uses a bagging classifier, which is one type of Ensemble Learning algorithm. To predict financial difficulties, the authors use the bagging classifier algorithm with 0.13% more accurate results than previous studies using the XGBoost algorithm.